Diskursus Kata “Membunuh” Dan “Menumpas” Dalam Ulangan 5:17; 7: 1-2: Humanisasi Atau Dehumanisasi: - Sihombing, Aeron Frior (Mitra Sriwijaya: Jurnal Teologi dan Pendidikan Kristen, 2025)
The problem addressed in this study is the apparent conflict between the word תִּֿרְצָֽח (trəṣāḥ, “to murder”) in Deuteronomy 5:17 and the term חָרַם (ḥāram, “to utterly destroy”) in Deuteronomy 7:2. This tension constitutes the primary research question of this study: do these two terms contradict one another, thereby resulting in dehumanization? The objective of this paper is to examine the discourse between trəṣāḥ and ḥāram. The theoretical framework employed is ideology of the Deuteronomistic redactor, which emphasizes the promotion of humanity through the Torah's legal traditions. The study applies redaction criticism and morphological analysis as its methodological approach. The findings indicate that the two terms do not contradict one another, as they stem from different redactional origins, contexts, and morphological structures.